CATALYTIC PYROLYSIS OF POLYPROPYLENE PLASTIC FROM MUNICIPAL SOLID WASTES INTO GASOLINE FRACTION COMPOUNDS USING THE MIXED NICKEL (Ni) AND CHROME (Cr) METALS AS THE CATALYST - Morina Morina; Oberlin Sidjabat (Testing Center for Oil and Gas LEMIGAS, 2014)
Plastic wastes which come from municipal solid wastes, have been identi􀂿 ed as the worldwideenvironmental problem in the last decades. Chemical recycling is one of the alternative methods to solvesuch problem. Inorder to obtai appropriate liquid fuels, polypropylene plastic waste was degraded thermallyand catalytically in the presence of natural zeolite incorporated with chromium (Cr) and nickel (Ni) metals.The reaction was conducted in a 􀂿 xed bed reactor in the temperature range of 400-500°C. The dependenciesof process temperature and effect of catalyst on yield of the fuel fractions were determined and comparedto commercial gasoline fractions. The current study shows that the major product of thermal degradation(pyrolysis) and catalytic degradation is liquid (gasoline) fraction and the highest products obtained attemperature 450°C is approximately 77.84%. The use of chromium and nickel metals on activated naturalzeolite as a bi-functional catalyst enhance the yield of liquid fractions and the acidity of the catalysts. The liquid product obtained in this process was analyzed using GC for its composition. Synthesized catalysts, activated natural zeolite and natural zeolite were characterized by means of nitrogen physisorption (BET), porosity, X-ray diffraction (XRD), and acidity. Based on the obtained results, the catalyst containing 6% of chromium and 4% of nickel on activated natural zeolite is a good catalyst for conversion of polypropylene plastic wastes to liquid (gasoline) fuels. Catalytic conversion using such catalysts may applicable as an alternative method for recycling plastic wastes to more valuable commodities such as fuel oils.